Analisis Budidaya Maggot Black Soldier Fly sebagai Solusi Pengelolaan Limbah Organik dalam Rantai Nilai Agroindustri di Kota Tasikmalaya - Salim; Nuriah, Neni (Cipasung Techno Pesantren: Jurnal Ilmiah, 2025)
Case study analysis of Maggot Al-Muttahid, a maggot cultivation business in Tasikmalaya City, shows its strategic role in reducing organic waste and improving the local economy in the agro-industrial sector. The city of Tasikmalaya faces serious challenges in managing organic waste, which encourages the search for sustainable solutions. One method that is increasingly recognized for its potential is the cultivation of Black Soldier Fly (BSF) maggots. This research aims to evaluate the effectiveness of BSF maggot cultivation in overcoming organic waste problems in the region, as well as assessing its contribution to increasing added value in the agro-industrial value chain. By using a value chain analysis approach and the Hayami added value calculation method, this research measures the economic contribution of the cultivation process. The research results show that BSF maggot cultivation is capable of bioconverting around 1,875 kg of organic waste in each cycle, which is converted into 75 kg of maggots. The resulting added value reached IDR 179.38 per kilogram with a value added ratio of 95.81%, indicating significant economic potential from this process.